Synthesis of Zeolite Using Aluminum Dross and Waste LCD Glass Powder: A Waste to Waste Integration Valorization Process - Yubin Kang; Basudev Swain; Byoungyong Im; Jin-Ho Yoon; Kwang Hoon Park; Chan Gi Lee; Dae Guen Kim (Metals, 2019)
In the current investigation, we synthesize zeolite using two different waste streams, such as aluminum dross and waste glass powder, for its potential application in indium and tin recovery from the leach liquor of waste liquid crystal display (LCD) glass. The aluminum dross (Al resource) and waste glass powder (Si resource) were used as raw materials for the synthesis of zeolite. Zeolite was synthesized using different weight ratios of Al dross and waste LCD glass by hydrothermal synthesis route using NaOH. The weight ratio variations of Al dross and waste LCD glass in this study are 0.3:1, 0.5:1, 1:1, 2:1, 3:1, and 4:1 using 2 M NaOH hydroxide by the hydrothermal technique. The synthesized zeolite was analyzed by X-ray diffraction spectroscopy (XRD), scanning electron microscopy (SEM), and Brunauer−Emmett−Teller (BET) followed by the possible application for recovery/extraction of indium and tin from leach liquor of waste LCD glasses. The indium extraction of average 93.66%, and tin extraction of 93.10% could be achieved from mixed solution indium and tin chloride. The significant achievement of the current investigation is that it can address two environment problems simultaneously, i.e., waste LCD glass and Al dross, and can be used for value recovery from waste LCD, LCD etching waste like secondary resources.